Nilai pH, Viskositas dan Hedonik Sari Buah Jeruk Manis dengan Penambahan Gelatin Tulang Ikan Bandeng - Bambang Dwiloka; Farhan Taufiqul Rahman; Sri Mulyani (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2021)
The stabilizer applied to sweet orange juice has properties as a clarifying agent, one of which is gelatin. Gelatin can be derived from collagen tissue of skin and bones animal, one of which is milkfish bone because fish contains high collagen. The effect of the clarifying agent on gelatin has an impact on sweet orange juice such as the degree of acidity, viscosity value and the level of consumer preference. This study aims to determine the values of pH, viscosity and hedonic for sweet orange juice with the addition of milkfish bone gelatin. The design of this study used completely randomized design with 5 treatments and 4 replications. The treatment given was the addition of milkfish bone gelatin to sweet orange juice, which was 0%; 0.2%; 0.4%; 0.6% and 0.8%. The data analysis method was carried out using the application of SPSS for windows 20.0. The results showed that the pH value was 4.695 to 4.733; viscosity value was 4.28 to 5.72 cP and hedonic scores 5 to 6 are obtained like to like very much. The best treatment in this study was the addition of 0.2% milkfish bone gelatin because it produced more efficient pH, viscosity and hedonic values.